In the Place of Philosophy - Korobczak, Paweł (Hybris, 2012)
In my paper, I refer to the Martin Heidegger's Letter on "Humanism", trying to reconsider the nature of philosophical thinking. I trace the motif of Heidegger's indication of the place of essential thinking as located before the separation of areas of theoria and praksis. It allows me to attempt a re-constitution of philosophy understood as a gesture related to both of them. It is significant in this contex to note the meaning of the name of philosophy itself in which emerges a strict relation between love and wisdom. So I focus on the question of love, as well as of related to it issues of humility or gift.